2020
DOI: 10.1158/1541-7786.mcr-19-1114
|View full text |Cite
|
Sign up to set email alerts
|

miR-106a Regulates Cell Proliferation and Autophagy by Targeting LKB1 in HPV-16–Associated Cervical Cancer

Abstract: ◥ miR-106a is aberrantly regulated in various tumors and plays an important role in carcinogenesis. However, the biological role and molecular mechanism by which miR-106a contributes to cervical squamous cell carcinoma (CSCC) remains elusive. In this study, we verified that miR-106a was elevated in both human papilloma virus (HPV) 16-positive CSCC tissues and cell lines. ROC curve analysis showed that miR-106a could well distinguish HPV-16-positive CSCC tissues from normal cervical squamous epithelium tissues.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…After further analyzing the cancer-promoting mechanism of miR-106a-5p, it was demonstrated that miR-106a-5p targeted and inhibited LKB1 levels. A recent study indicated that in HPV-16-associated cervical cancer, LKB1 regulated proliferation and autophagy, and its expression level was targeted by miR-106a (49). In the present study, overexpression of LKB1 inhibited the proliferation and migration, and promoted autophagy of Calu-3 and NCI-H661 cells.…”
Section: Discussionsupporting
confidence: 61%
“…After further analyzing the cancer-promoting mechanism of miR-106a-5p, it was demonstrated that miR-106a-5p targeted and inhibited LKB1 levels. A recent study indicated that in HPV-16-associated cervical cancer, LKB1 regulated proliferation and autophagy, and its expression level was targeted by miR-106a (49). In the present study, overexpression of LKB1 inhibited the proliferation and migration, and promoted autophagy of Calu-3 and NCI-H661 cells.…”
Section: Discussionsupporting
confidence: 61%
“…Activation of Akt can activate the downstream mTOR, thereby reducing the expression of Beclin-1 and LC3 and inhibiting autophagy. Studies have shown that DDP can activate Akt/mTOR pathway and cause drug resistance in bladder cancer, ovarian cancer and nasopharyngeal carcinoma [18] . PI3K/Akt/mTOR signaling pathway can stimulate cell growth in multiple stages of cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-106a-5p was reported to be dysregulated in various of diseases, such as prostate cancer (23), atherosclerosis (24) and cervical cancer (25). The clinical value of miR-106a-5p in diseases attracted researcher attention.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Zhang et al, miR-106a-5p level was downregulated in osteoarthritis (OA) samples and IL-1b-treated chondrocytes, miR-106a-5p overexpression led to proliferation promotion and apoptosis inhibition in chondrocytes treated by IL-1β (26). Another study in HPV-16-associated cervical cancer reported that miR-106a-5p played an important role in regulatory mechanism of cervical squamous cell carcinoma (CSCC) and could be a potential therapeutic target in HPV-associated cervical cancer (25). Considering the dysregulation of miR-106a-5p in the serum of psoriasis patients, we further explored whether serum miR-106a-5p could differentiate between the psoriasis patients and the healthy.…”
Section: Discussionmentioning
confidence: 99%